A MODEL OF ADAPTIVE LEARNING IN SMART CLASSROOMS BASED ON THE LEARNING STRATEGIES - Radosavljevic, Vitomir; Radosavljevic, Slavica; Jelic, Gordana (PEOPLE: International Journal of Social Sciences, 2019)
The paper presents a proposal of a model of adaptive learning. The model takes the advantage of a smart classroom environment for the realization of adaptive learning. As adaptation criteria, it uses parameters of motivation, student’s prior knowledge, cognitive load and a dynamic environmental parameter. The dynamic environmental parameter is a parameter which is obtained by evaluating physical parameters of working environment in a smart classroom. The learning process is carried out through different learning strategies grouped in learning categories. The model dedicates a learning category to a student based on a formula which takes in consideration above mentioned adaptation criteria The proposed model has been tested. The assessment test scores at the end of a learning process showed that student’s in the experimental group achieved better learning outcomes than the student’s who learned in a traditional manner. The obtained results are encouraging and lay a sound foundation for the application and further development of the model.